Hubungan Status Menarche Ibu dengan Menarche Remaja Putri Kelas IX di SMPN 1 Pelabuhan Ratu - widyaningsih, eka bati (Jurnal Kesehatan Abdurrahman, 2026)
Menarche is the first menstruation experienced by adolescent girls and serves as an important marker in the transition toward puberty and reproductive maturity. This event is not merely a biological phenomenon but also reflects the development of the reproductive system, which is influenced by various factors, particularly genetic or biological factors. This study aimed to analyze the relationship between mothers’ menarche status and the age at menarche among ninth-grade female students at SMPN 1 Pelabuhan Ratu. The research used a quantitative approach with a purposive sampling technique. Out of a total population of 212 adolescents, 139 respondents met the inclusion and exclusion criteria and were selected as the study sample. The main variables in this study included mothers’ menarche status and the age at menarche of adolescent girls. Data were collected using questionnaires and were analyzed using statistical tests through the SPSS program. The results show that 47.5% of adolescents experience early menarche, 43.9% experience normal menarche, and 8.6% experience late menarche. Statistical analysis yields a p-value of 0.00, indicating a significant relationship between mothers’ age at menarche and their daughters’ age at menarche. Thus, the earlier a mother experiences menarche, the earlier her daughter experiences it as well, demonstrating that genetic factors and family environment play a major role in determining adolescents’ age at menarche.